Development of Prototype of Arduino-Based Automatic Ablution Faucet to Save Water Usage - Al Imran; Firdaus Firdaus; Haripuddin Haripuddin; Abdillah Jamil (Jurusan Pendidikan Teknik Elektro, 2025)
This study aims to develop and evaluate an Arduino-based automatic ablution faucet designed to reduce water consumption through proximity sensing and real-time water-flow monitoring. Using an engineering research approach with a prototype development model, the system was constructed using an Arduino Uno microcontroller, a proximity sensor, and a water-flow sensor, followed by direct testing and usability evaluation involving 30 respondents. Functionality assessment was conducted by experts using the ISO 25010 framework, while usability testing employed a Likert-scale questionnaire. The results show that the automatic faucet successfully regulated water flow based on user presence and displayed real-time water usage on an LCD. Comparative testing between manual and automatic faucets demonstrated a 44.03% reduction in water consumption, with the prototype achieving 100% functionality and an 87.8% usability score, indicating that the system is operationally reliable, accurate, and user-friendly. Sensor calibration produced an average error rate of 1.2%, which falls within acceptable tolerance limits. The novelty of this research lies in its integration of dual-sensor technology, quantitative water-efficiency measurement, and ISO 25010-based quality evaluation within a single prototype framework an approach not commonly adopted in previous studies on ablution automation. The incorporation of real-time water monitoring also enhances the system’s practicality and contributes to technological advancements in water conservation and electrical engineering applications.